Evaluation of the Impact of Public Service Development Programs in Boliyohuto District, Gorontalo Regency - Katijan, Ainun Riska; Pakudu, Robin; Karim, Dian Fitriani; Idji, Rusly Abdurahman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The purpose of this study is to ascertain the effects of public service development initiatives. The research methodology combines a descriptive research design with a qualitative approach. The community, the heads of Sidomulyo and Sidodadi villages, the district secretary, and the head of Boliyohuto district served as the main sources of data for this study. Methods for gathering research data include documentation, interviews, and observation. According to the research findings, two indicators—political and administrative feasibility—are optimal, while three indicators—effectiveness, efficiency, and justice—are not yet at their best because a number of elements still need to be improved. Though not yet completely functional, the development of publik services in Boliyohuto District has been executed well. Since the people are the ones who experience this influence, several things still need to be adjusted in order for the publik services development in Boliyohuto District to proceed smoothly. Based on the research results, it can be concluded that of the five evaluation indicators, researchers found three indicators that were not optimal, including effectiveness, efficiency, and justice. Then there are two indicators that have been running optimally, including political feasibility and administrative feasibility.